Security study of data storage and communication in internet-PC environment - Tan, Benson Wei Jin. (2010)
A large amount of data and information is sent and received everyday via the Internet for various purposes. Most of these data contain private information that individuals would like to be kept secret. The challenge in data privacy is to be able to share data with relevant personnel while protecting important information from access by adversaries.